2013
DOI: 10.1103/physrevb.88.104417
|View full text |Cite
|
Sign up to set email alerts
|

Dzyaloshinskii-Moriya driven helical-butterfly structure in Ba3NbFe3Si2Oet al.

Abstract: International audienceWe have used soft x-ray magnetic diffraction at the Fe3+ L2,3 edges to examine to what extent the Dzyaloshinsky-Moriya interaction in Ba3NbFe3Si2O14 influences its low-temperature magnetic structure. A modulated component of the moments along the c axis is present, adding to the previously proposed helical magnetic configuration of coplanar moments in the a,b plane. This leads to a "helical-butterfly" structure and suggests that both the multiaxial in-plane and the uniform out-of-plane Dz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 63 publications
5
37
0
Order By: Relevance
“…From the perspective of neutron scattering using enantiopure single crystals, it was determined that the moments lie within the ab plane and propagate in a circular helix along the c axis with propagation vector l¼ (0, 0, 0.142) [8,9]. Using resonant x-ray scattering it was found that there is an additional small c axis component that modulates with a sine curve along l [22], but Fig. 9.…”
Section: Magnetic Structure Of Pb 3 Temn 3 P 2 O 14mentioning
confidence: 98%
See 2 more Smart Citations
“…From the perspective of neutron scattering using enantiopure single crystals, it was determined that the moments lie within the ab plane and propagate in a circular helix along the c axis with propagation vector l¼ (0, 0, 0.142) [8,9]. Using resonant x-ray scattering it was found that there is an additional small c axis component that modulates with a sine curve along l [22], but Fig. 9.…”
Section: Magnetic Structure Of Pb 3 Temn 3 P 2 O 14mentioning
confidence: 98%
“…Here, k 0 is of the same form found in Ba 3 NbFe 3 Si 2 O 14 . Using this approximation, a magnetic structure refinement was made using IR Γ 1 with k 0 in accordance with Ba 3 NbFe 3 Si 2 O 14 [22], where all moments were constrained to point within the ab plane (Fig. 5).…”
Section: Magnetic Structure Of Pb 3 Temn 3 P 2 O 14mentioning
confidence: 99%
See 1 more Smart Citation
“…One sort of spin chirality which is selected by the sign of DM (Dzyaloshinsky-Moria) vector,D, in the antisymmetric DM interactioñ D ÁS i ÂS j , fixes the spin helicity. 13 Thus, the magnetic ground state in zero magnetic field forms a single magnetic domain which was observed by the neutron diffraction 14,15 and electron spin resonance (ESR) 16 experiments.…”
mentioning
confidence: 97%
“…Prominent examples include Cr 1/3 NbS 2 (space group P 6 3 22) [36] and the trigonal chiral compound Ba 3 NbFe 3 Si 2 O 14 (space group P 321) [37][38][39], which displays structurally enantiopure crystals with single magnetic chirality. The accumulation of experimental data on the coupling between structural and magnetic chiralities is a necessary condition not only for understanding the underlying microscopic mechanisms but also for developing the control of exotic magnetic textures as is widely discussed in the context of potential spintronics applications [18,40].…”
mentioning
confidence: 99%